2018
DOI: 10.1177/1120700018776311
|View full text |Cite
|
Sign up to set email alerts
|

Is computerised 3D templating more accurate than 2D templating to predict size of components in primary total hip arthroplasty?

Abstract: Our results support the superiority of 3D templating over 2D templating in predicting implant size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 31 publications
(53 reference statements)
0
46
0
Order By: Relevance
“…The results showed that the complete accuracy rate of acetabular cup was 7.3%, that of one size was 41%, that of femoral stem was 34%, and that of one size was 76%. Shaarani et al [17] carried out preoperative planning for 100 patients with the same digital template. The results showed that the complete accuracy rate of the acetabular cup was 38%, one size was 80%, and the complete accuracy rate of the femoral stem was 36%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the complete accuracy rate of acetabular cup was 7.3%, that of one size was 41%, that of femoral stem was 34%, and that of one size was 76%. Shaarani et al [17] carried out preoperative planning for 100 patients with the same digital template. The results showed that the complete accuracy rate of the acetabular cup was 38%, one size was 80%, and the complete accuracy rate of the femoral stem was 36%.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's standard pelvic anteroposterior X-ray was imported into the 2D digital template (Smart joint, Depuy Synthes), and the diameter of the marker ball was set to 38mm. The digital template prosthesis was superimposed on the AP pelvic radiograph, and the optimal size of the prosthesis was selected according to the matching situation between the: acetabular cup, the acetabulum, femoral stem, and femoral medullary cavity [17] (Fig. 7).…”
Section: D Group Preoperative Planningmentioning
confidence: 99%
“…The patient's standard pelvic anteroposterior X-ray was imported into the 2D digital template (Smart joint, Depuy Synthes), and the diameter of the marker ball was set to 38 mm. The digital template prosthesis was superimposed on the AP pelvic radiograph, and the optimal size of the prosthesis was selected according to the matching situation between the acetabular cup and the acetabulum, femoral stem, and femoral medullary cavity [21] (Fig. 7).…”
Section: D Group Preoperative Planningmentioning
confidence: 99%
“…Several new technologies, such as preoperative three-dimensional (3D) templating and intraoperative navigation, have been used to avoid inadequate stem selection and achieve better stem positioning. Schiffner et al reported that the accuracy of predicting the right stem size improved from 45.7% to 58.6% using 3D templating compared with 2D surgical planning 8 . Weber et al found similar accuracy in biomechanical hip reconstruction of the leg length and global and femoral offset in THA between intraoperative navigation and uoroscopy 9 .…”
Section: Introductionmentioning
confidence: 99%